2002
DOI: 10.1081/cnv-120002491
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Colon Cancer Cell Apoptosis by 5-Fluorouracil in Humans

Abstract: To assess the mechanism of action of 5-fluorouracil (5-FU) apoptosis (AI) and proliferation (PI) indices were determined histochemically in colon carcinoma and normal colon tissue of 7 patients treated preoperatively with 5-FU (300 mg/m2/day for 5 days) and 11 controls. 5-Fluorouracil induced apoptosis selectively in malignant colonocytes (AI in 5-FU-group: 0.126 +/- 0.016 [mean +/- SEM] vs. 0.065 +/- 0.012 in controls; P < 0.05), but not in normal colonocytes. 5-Fluorouracil had no effect on the PI of either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In RKO-EcR-KLF4 cells treated with Ponasterone A to induce KLF4, we see no evidence of nuclear condensation, chromatin fragmentation, apoptotic bodies, or plasma membrane disruption. In contrast, RKO-EcR-KLF4 cells treated with 5-FU, a known proapoptotic agent (Rigas et al, 2002), exhibit these morphological changes. Figure 4b shows results of electrophoresis of genomic DNA from RKO-EcR and RKO-EcR-KLF4 cells treated with Ponasterone A, ethanol, or 5-FU.…”
Section: Klf4 Overexpression Does Not Induce Apoptosismentioning
confidence: 89%
“…In RKO-EcR-KLF4 cells treated with Ponasterone A to induce KLF4, we see no evidence of nuclear condensation, chromatin fragmentation, apoptotic bodies, or plasma membrane disruption. In contrast, RKO-EcR-KLF4 cells treated with 5-FU, a known proapoptotic agent (Rigas et al, 2002), exhibit these morphological changes. Figure 4b shows results of electrophoresis of genomic DNA from RKO-EcR and RKO-EcR-KLF4 cells treated with Ponasterone A, ethanol, or 5-FU.…”
Section: Klf4 Overexpression Does Not Induce Apoptosismentioning
confidence: 89%
“…Apoptosis is one such important cellular response and both in vitro and in vivo studies have effectively demonstrated that activation of the apoptotic pathways contributes to the cytotoxic action of most chemotherapeutic drugs [45,46]. Both 5-FU and oxaliplatin, two of the main chemotherapeutic agents used in treatment of advanced CRC act by selective induction of apoptosis in colon cancer cells [47,48]. Also combination treatment with 5-FU and irinotecan has been shown to induce apoptosis in various colon carcinoma cell lines [49,50].…”
Section: Chemotherapy and Apoptosis In Colorectal Cancermentioning
confidence: 99%
“…Like most chemotherapeutic agents, 5-FU alone and in conjunction with folinic acid induces marked apoptosis in sensitive cells. Specifically, 5-FU has been shown to induce apoptosis in colonocytes and colon cancer cells [4,5].…”
Section: Introductionmentioning
confidence: 99%